STUDY TECNOLOGY OF LONGLINE FISHING GEAR IN THE MUARA SAKO KAMPAR KIRI WATER’S LANGGAM VILLAGE PELALAWAN REGENCY - Siregar, Arfan Efendi; Brown, Arthur; ', Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in May 2016 in the Langgam villages, Pelalawan Regency’s. This study aimed to analyze aspects relating to technological aspects of environmental friendliness and business feasibility. The method used is a survey method.The result showed that gear can be classified as a very environmental friendlygear with 33 score. In term of the feasibility study this kind of tecnology is benefit operated.(BCR: 2,3, 207,1% of FRR and with 0,5 years payback period).Keywords: longline, environmental friendliness, business feasbility